2018
DOI: 10.1002/dac.3820
|View full text |Cite
|
Sign up to set email alerts
|

Joint sensing time and fusion rule threshold optimization for energy efficient CSS in cognitive radio sensor networks

Abstract: Energy resources become precious when the secondary users (SUs) in cognitive radio (CR) network are battery operated, especially in cooperative spectrum sensing (CSS). So it becomes important to use their energy efficiently. In CSS, the number of cooperative users, fusion rule threshold, transmission power, and sensing time affects the energy efficiency (EE) of the CSS. In this paper, an iterative algorithm is proposed to determine joint optimal fusion rule threshold and sensing time that maximizes the EE of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Here, we give a brief overview of the related works with the state-of-the-art schemes and algorithms adopted in the existing literature. To maximize EE, whereas encountered the required detection accuracy, [5] proposed an iterative algorithm to change the fusion threshold on optimal sensing length. The authors showed their proposed parameters while satisfying the detection accuracy constraints for EE maximization.…”
Section: A Related Workmentioning
confidence: 99%
“…Here, we give a brief overview of the related works with the state-of-the-art schemes and algorithms adopted in the existing literature. To maximize EE, whereas encountered the required detection accuracy, [5] proposed an iterative algorithm to change the fusion threshold on optimal sensing length. The authors showed their proposed parameters while satisfying the detection accuracy constraints for EE maximization.…”
Section: A Related Workmentioning
confidence: 99%